Population structure and genetic diversity of Magnolia cubensis subsp. acunae (Magnoliaceae): effects of habitat fragmentation and implications for conservation. Issue 4 (19th July 2020) - Hernández, Majela; Palmarola, Alejandro; Veltjen, Emily; Asselman, Pieter; Testé, Ernesto; Larridon, Isabel; Samain, Marie-Stéphanie; González-Torres, Luis R.
Abstract: Genetic data on threatened plant populations can facilitate the development of adequate conservation strategies to reduce extinction risk. Such data are particularly important for species affected by habitat fragmentation such as Magnolia cubensis subsp. acunae, a Critically Endangered magnolia subspecies endemic to Cuba. Using genetic data from 67 individuals, we aimed to evaluate the effect of habitat fragmentation on two subpopulations in the Guamuhaya mountain range, in Topes de Collantes Protected Natural Landscape and Lomas de Banao Ecological Reserve. We characterize the structure and genetic diversity of these subpopulations, with the objective of managing their conservation more effectively. We used Landsat satellite images to determine land-cover types at the two locations and calculated indices of habitat fragmentation. For genetic analyses, we extracted DNA from the leaf tissue of individuals from the two subpopulations and used 11 microsatellite markers to genotype them. We calculated heterozygosity, allelic richness and the F -statistics, to evaluate genetic variability. The montane rainforest in Topes de Collantes was most affected by habitat fragmentation, with smaller patches of more irregular shapes, compared to submontane forest at this location and both montane and submontane forests in Lomas de Banao. Genetic diversity was higher in Topes de Collantes, but we found no genetic differentiation between subpopulations. Our findings suggest the two subpopulations can be considered a single evolutionary unit and conservation entity. We propose to use individuals from both subpopulations for reinforcement to increase the overall genetic diversity of the subspecies.